Cake - Kalman, Maira; Scott-Goodman, Barbara (New York : Penguin Press, 2018)
"With great style, wit, and joy, Maira Kalman and Barbara Scott-Goodman celebrate their favorite dessert. In Cake, renowned artist and author Maira Kalman and food writer Barbara Scott-Goodman bring us a beautifully illustrated book dedicated to their mutual love of cakes. Kalman's enchanting illustrations, in her inimitable style, and Scott-Goodman's mouthwatering recipes complement each other perfectly, making Cake a joyful whimsical celebration of a timeless dessert"--
boek